Analysis Of Students' Difficulties In Writing Recount Texts At The Secend Semester Of Institut Penddikan Nusantara Gelobal Academic Year 2022/2023 - Muhsinin, Muhsinin (Lembaga Bale Literasi, 2023)
Problems often faced by students when writing. They often get stuck and seem to have difficulty expressing their ideas in written form. From the assessments carried out by lecturers, students often find many errors in writing chapter reports. Finally, the most common errors are found in content aspects, such as grammar, vocabulary, punctuation, etc. What are the students' difficulties in writing recount texts for the even semester of the Gelobal Nusantara Education Institute for the 2022/2023 academic year?